Pengaruh Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loan, Operational Efficiency dan Ukuran Perusahaan terhadap Harga Saham dengan Profitabilitas sebagai Variabel Intervening - Nana Sepdiana (JAS (Jurnal Akuntansi Syariah), 2017)
This study aims to analyze The Influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), Operational Efficiency (BOPO) and firm size (Size) on price stock with Profitability as an Intervening Variable in Bank Umum Swasta Nasional Listed at BEI. The study of population is Bank Umum Swasta Nasional Listed at BEI from the year 2010 – 2014. The method of determination is sampling by using purposive sampling. The variable is used price stock as endorgen, CAR, LDR, NPL, BOPO, and size as eksogen, then ROA as an intervening variable. To examine research hypotheses by using path analysis that assisted SPSS 17 for windows. The result of research CAR and LDR effected positive significance toward ROA. BOPO effected negative significance toward ROA. Whereas NPL and size not effected significance toward ROA. CAR and BOPO effected positive significance toward contribution value. NPL effected negative significance toward price stocks. Wheares LDR and size not effected significance toward price stocks. ROA effected positive significance toward price stocks. ROA effected positive significance toward price stocks. CAR, LDR, NPL, BOPO and size not effected significant toward price stocks by means of ROA mediation. As suggested, this research is already done at Bank Umum Swasta Nasional. So, for the next research, need to add another variable that can effect price stocks. As a result, the price stocks of banks can increase significantly.